BRIDGING LANGUAGE BARRIERS IN RURAL TOURISM: A STRATEGIC COMMUNICATION MODEL FOR KADUGENEP VILLAGE - Ria Saraswati; Malabay Malabay; Yulianti Yulianti (Getsempena English Education Journal, 2025)
This study aims to develop a strategic communication model for Kadugenep Village to enhance cross-language interactions between local residents and tourists. Employing a mixed-method approach, the research collected qualitative data through interviews and focus group discussions with villagers, tourism stakeholders, and language educators, while a quantitative survey assessed the current linguistic capabilities and communication barriers. The data were also analyzed using using thematic analysis to summarize the villagers’ linguistic abilities and identify the most common communication barriers. The findings revealed that villagers express enthusiasm for engaging with tourists, limited access to formal language education and a lack of practical communication tools pose significant challenges. The proposed model incorporates a combination of basic language training, non-verbal communication strategies, and mobile translation applications to facilitate more effective interactions. The study concludes that a structured yet flexible approach to language learning, adapted to local needs and resources, can significantly improve rural communities’ participation in the tourism economy. Implementing this model in Kadugenep Village has the potential to not only enhance visitor experiences but also promote sustainable tourism development. Future research should explore how similar models can be adapted to other rural tourism destinations with varying linguistic and cultural contexts.